Factors associated with medical complications after body art among Israeli adults: a retrospective study - Liat Korn; Hagit Bonny-Noach; Gideon Koren; Rachel Nissanholtz-Gannot (BMC, 2021)
Abstract Introduction Body-art, including tattoos and piercings, is steadily increasing world-wide but with relatively limited reporting of adverse outcomes. The objective of the present study was to identify correlates that would facilitate a preventative strategy to minimize adverse effects of body-art. Methods We examined patterns of body-art, health risk and perceptions among 921 participants (54% female, mean age of 35; SD = 10.8) through in-person questionnaire. Results A significantly lower frequency of those with body-art acknowledged that not all venues (parlors, clinics, etc.) are safe in terms of health and hygiene (84.7%t vs. 96.6%, p < .001) as compared to those without body-art. Similarly, knowledge of the need for a Ministry of Health certification was reported with lower frequency (77.2% vs. 94.5%, p < .001) among those with body-art. Those who experienced medical complications reported higher frequencies of smoking cigarettes and hookah as well as using ecstasy (MDMA). The risk of medical complication after body-art was 4 times higher in those who used ecstasy (OR = 3.97; CI 1.0-14.4; p < 0.05). In addition, it was more than 3 times higher for street or home tattooing as compared to studio or a licensed medical center (OR = 3.59; CI 1.32-9.76; p < .01), as well as almost 3 times higher among those who did not receive information before performing body-art (OR = 2.70; CI 1.05-6.92; p < .05) and who had somebody other than themselves decide on the body-art design (OR = 2.68; CI 1.00-7.19; p < .05). Conclusions A targeted informational-preventative program should be developed, informed by the risks highlighted in this study. In addition, it would be necessary to draft policies related to regulation and enforcement in order to more effectively manage body-art service provision. The Ministry of Health should supervise and guide tattooists and practitioners regarding the health risks of body-art and offer training and raise awareness among potential clients.